Jarik Bekti Pertiwi: Desain Motif dan Aplikasinya dalam Ritual Gemblang Samin, Bojonegoro, Jawa Timur - Wardoyo, Sugeng; Wulandari, Tri (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2024)
This study discusses the design of jarik artifacts used in the Gemblang ritual for the people of Samin Bojonegoro. So far, there has yet to be design research on jarik artifacts for Gemblang ritual facilities. Esensi pitutur luhur Samin became the concept of jarik design. This study aims to make jarik used in the Gemblang ritual as a medium of cultural preservation that strengthens Samin's noble speech. This design uses practice-led research methods, visual metaphors, and vehicle switching. The stages of research are the steps of observation, data collection, data analysis, and presentation of analysis results. The results of the analysis become the concept of designing batik motif designs. The design process involves preparation, imagination, development, and craftmanship steps. The result of the design is in the form of a prototype of Bekti Pertiwi as the cultural identity of the people of S amin Bojonegoro. Jarik Bekti Pertiwi has the primary function of completeness of Samin elders' clothing and is part of the ritual facilities in the Gemblang ritual.